Prospective study on sociodynamics of cellulitis in general surgical unit - Chakravarthy, Didde Sundara; Gandeti, Kiran Kumar; GS, Subramanyam; Yeddula, Venkata Jayaramudu; Gera, Arjuna (International Journal of Research in Medical Sciences, 2017)
Background: Cellulitis is a potentially serious infection that commonly recurs. The identification of preventable dynamic factors could reduce infection related morbidity and cost and improve patient management. The aim of this study was to identify the dynamic factors associated with cellulitis, including analysis of risk factors associated with cellulitis in either limb and in other parts of the body. Methods: We conducted a prospective study on 110 patients with cellulitis in either limb and in other parts of the body, who were admitted in septic ward of all units of King George hospital between period of December 2013 to December 2014. The factors such as low socioeconomic status, illiteracy, rural area, nutritional status and associated co-morbid conditions and their effect on outcome of patient were studied. Univariate analyses were performed to describe the study. Results: The median age of the participants was 62.5 years. The following risk factors were strongly and independently associated with cellulitis and outcome of the patient; illiteracy (OR, 4; P value 0.010), age above 50 years (OR, 0.110; P value 0.000), residing in rural areas (OR, 4.008; P value 0.006), low socioeconomic status (OR, 0.241; P value 0.030) and associated co-morbid conditions (OR, 0.390; P value, 0.032). Conclusion: Patients usually presented in the late stage of disease because of illiteracy, ignorance and poor knowledge. Patients should be educated to routinely inspect their feet, and the importance of appropriate footwear should be emphasized. Patients who are actively involved in their care can improve their quality of life and have a better outcome.